The Rise of Irregular Domestic Work Amongst Female Migrants in Italy - Romeo, Elena (AUC Knowledge Fountain, 2023)
In today’s globalized world, hardship and geopolitical and economic crises have led to the lack of decent work, and this resulted in new, migratory movements. Women have joined these migration flows in growing numbers, which has important consequences for gender equality in both countries of origin and destination (ILO,2015). Hence, migration has a new character, and it includes many women who emigrate from their country because of a lack of access and choices to jobs, exploitation, and lower wages compared to men in Europe. In this context, one can affirm that today irregular migration is on the rise, especially in the South of Europe, not only because of the strategic geographical position of these countries, which are easy to reach by sea but also because of a change in the demand of the labour market, where cheap female domestic work is rapidly spreading. Therefore, the main purpose of this study is to fill the gap in the literature and explain the persistence of irregular domestic work through a gendered lens. I will draw on interview data with domestic migrant workers and examine the results to discuss my findings.